MANIFESTATIONS OF NSAID-GASTRODUODENOPATHY IN PATIENTS WITH KNEE OSTEOARTHRITIS. (LITERATURE REVIEW) - Azimova M.M; Khudayberganova N.X; Khadjimatova I.X (Scholar Express Journals, 2023)
The article presents the effect of non-steroidal anti-inflammatory drugs (NSAIDs) on the gastrointestinal tract (GIT) and the pathogenesis of gastroduodenopathy in patients with knee osteoarthritis (KOA)
Keywords: osteoarthritis; gonarthrosis; non-steroidal anti-inflammatory drugs